Authorities and Mechanisms for Purchased Care at the Department of Veterans Affairs - Health, RAND (RAND Corporation, 2015)
The Department of Veterans Affairs (VA) furnishes purchased care services through an array of programs, each with different eligibility requirements and payment processes. A RAND study revealed inconsistencies in procedures, unclear goals, and a lack of cohesive strategy for purchased care, which could have ramifications for veterans' access to care.